Preparation method of core-shell cu-btc@tpa-1 polyethylene glycol film with ordered hierarchical hierarchical pores

CN118267860BActive Publication Date: 2026-10-09ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410174310.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2026-10-09
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

但这些MOF混合基质膜均是通过传统制备技术获得,普遍存在气体传质阻力大、渗透系数低的问题

Benefits of technology

[0026] 1. This invention constructs a core-shell hybrid MOF in COF, which enhances the gas separation performance of porous materials in membranes. The MOF acts as a shell surrounding the COF core, and its internal microporous structure functions as a molecular sieve in gas separation. Gases with larger molecular dynamic diameters are repelled from the MOF channels, while gases with smaller molecular dynamic diameters can enter the MOF channels and be transported into the COF channels. The macroporous environment in the COF provides a low mass transfer resistance channel for gas molecule transport, facilitating rapid gas passage. Cu-BTC@TpPa-1 exhibits an ideal adsorption selectivity of 37 for CO2 and N2 at 298 K and 1 bar, respectively, representing improvements of 85% and 143% compared to pure Cu-BTC and pure TpPa-1.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118267860B_ABST
    Figure CN118267860B_ABST
Patent Text Reader

Abstract

The application relates to a gas separation membrane technology and aims to provide a preparation method of a core-shell Cu-BTC@TpPa-1 polyethylene glycol membrane with ordered layered multi-stage pores. The method comprises the following steps: mixing Tp, Pa, mesitylene, dioxane and acetic acid, and obtaining a covalent organic framework TpPa-1 through a centrifugal method; then mixing and stirring the TpPa-1 with PVP, and performing drying treatment to obtain TpPa-1 loaded with PVP; then reacting the TpPa-1 with Cu(NO3)2.3H2O and mesitylene to form a copper-based metal organic framework Cu-BTC in situ on the surface of the TpPa-1, thereby obtaining a Cu-BTC@TpPa-1 in a core-shell structure; finally mixing the Cu-BTC@TpPa-1 with PEGDA and AIBN, pressing a film, and performing heat cross-linking plasticization molding to obtain a Cu-BTC@TpPa-1 polyethylene glycol membrane. The application can improve the gas separation effect of the porous material in the membrane, is helpful for realizing the rapid passing of the gas, can effectively improve the solubility and diffusivity of CO2 in the membrane, reduces the mass transfer resistance, improves the CO2 permeation coefficient and CO2 / N2 selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gas separation membranes, specifically the preparation method and application of thermally crosslinked polyethylene glycol membranes with ordered hierarchical multi-level porous core-shell Cu-BTC@TpPa-1 composite adsorbent. Background Technology

[0002] High atmospheric CO2 concentrations contribute to global warming and frequent extreme weather events, making CO2 emission control a significant challenge for modern society. Membrane separation of CO2 technology primarily uses selectively permeable membranes as the separation medium, driven by the partial pressure or concentration difference of CO2 gas across the membrane, and leverages the different permeation rates of various gas components within the membrane material to achieve CO2 separation. Due to its advantages such as low energy consumption, high efficiency, and environmental friendliness, it has become a hot research and development topic both domestically and internationally in recent years. However, traditional rubber-based polymer membranes are limited by the trade-off between permeability and selectivity; that is, membranes with higher permeability have lower selectivity, and vice versa. To overcome this constraint, hybrid matrix membranes are prepared by introducing porous media such as metal-organic frameworks, graphene oxide, and zeolites into polymer matrices, which can significantly improve both permeability and selectivity in gas separation.

[0003] Covalent organic frameworks (COFs) are a new class of crystalline porous materials formed by the precise atomic integration of organic units through strong covalent bonds. They possess characteristics such as strong thermochemical stability, high pore volume, large pore size, well-defined pore structure, and tunable functional groups, and are mainly used in catalysis, gas storage, drug delivery, optoelectronic materials, and supercapacitors. Metal-organic frameworks (MOFs) are organic-inorganic hybrid compounds composed of organic linkers and inorganic multi-metal units. Compared to COFs, MOFs typically have smaller pore sizes, closer to the dynamic diameter of gas molecules, and are therefore frequently used in gas separation. Generally, the properties of MOFs depend on their structure, including their composition and system architecture. Therefore, the rational design of MOF structural parameters is of great significance for their applications in various fields. Constructing MOF-based hybrid materials is a new method to broaden the composition and properties of MOF-based materials.

[0004] Bu et al. coated a layer of COF material TpPa-1 onto a porous alumina support, and then grew a layer of MOF material ZIF-9 in situ on its surface to prepare a continuous-phase rigid membrane exhibiting a high H2 permeability coefficient. Fan et al. coated a layer of COF material TpPa-1 onto a porous alumina support, and then grew a layer of MOF material ZIF-67 in situ within it to prepare a continuous-phase rigid membrane exhibiting a high H2 permeability coefficient and H2 / CO2 and H2 / CH4 selectivity. Zhang et al. grew a layer of COF material TpPt in situ on the surface of Ti-MOF, forming a MOF-in-COF core-shell structure, which exhibited high catalytic activity. However, these MOF mixed matrix membranes were all obtained through traditional preparation techniques, and generally suffer from high gas mass transfer resistance and low permeability coefficients. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing an ordered, hierarchical, multi-level porous core-shell Cu-BTC@TpPa-1 polyethylene glycol membrane.

[0006] To achieve the above objectives, the solution of the present invention is:

[0007] A method for preparing an ordered, hierarchical, multi-level porous core-shell Cu-BTC@TpPa-1 polyethylene glycol membrane is provided, comprising the following steps:

[0008] (1) According to the dosage relationship of 0.63g:0.48g:15ml:15ml:5ml, triformylphloroglucinol (Tp), p-phenylenediamine (Pa), mesitylene, dioxane and acetic acid aqueous solution with a concentration of 3mol / L were added to a heat-resistant glass container; after sonication until completely dissolved, the mixture was degassed by freeze-thaw cycle 3 times; the heat-resistant glass container was sealed and evacuated, and heated at 120℃ for 72 hours; the reaction precipitate was obtained by centrifugation, and washed multiple times with tetrahydrofuran and acetone respectively; after vacuum drying, a dark red powdery covalent organic framework TpPa-1 was obtained.

[0009] (2) Weigh TpPa-1 and polyvinylpyrrolidone (PVP) as a surfactant at a mass ratio of 2:1. First, dissolve TpPa-1 in an ethanol solution, then add polyvinylpyrrolidone (PVP) and stir for 2 hours. After vacuum drying, TpPa-1 loaded with PVP is obtained.

[0010] (3) Weigh out PVP-loaded TpPa-1, Cu(NO3)2·3H2O and mesitylene according to a mass ratio of 100:33~330:67~670 respectively; first disperse the PVP-loaded TpPa-1 in methanol, dissolve Cu(NO3)2·3H2O in deionized water, and dissolve mesitylene in ethanol solution, then mix and stir until uniform; introduce the mixture into a polytetrafluoroethylene reactor, react at 110℃ for 48 hours, and a copper-based metal-organic framework Cu-BTC is grown in situ on the surface of TpPa-1; collect the solid product by centrifugation, purify it several times with methanol; after vacuum drying, obtain Cu-BTC@TpPa-1 with a core-shell structure;

[0011] (4) Weigh Cu-BTC@TpPa-1, polyethylene glycol diacrylate (PEGDA) and azobisisobutyronitrile (AIBN) as a crosslinking agent according to a mass ratio of 20-220:1000:5, mix and stir thoroughly to obtain a mixture; spread the mixture on a glass plate, take another glass plate and press it on its surface, and use a spacer between the glass plates to control the film thickness; transfer the above components to a 70°C oven for thermal crosslinking and plasticizing to obtain Cu-BTC@TpPa-1 polyethylene glycol film.

[0012] As a preferred embodiment of the present invention, in steps (1) to (3), vacuum drying refers to drying in a vacuum oven at 120°C for 12 hours.

[0013] As a preferred embodiment of the present invention, the cleaning operation in step (1) includes: first exchanging the solvent with tetrahydrofuran 3 times, each time for 12 hours; then exchanging the solvent with acetone 3 times, each time for 12 hours.

[0014] As a preferred embodiment of the present invention, in step (4), the thickness of the gasket is 200 μm.

[0015] As a preferred embodiment of the present invention, the Cu-BTC@TpPa-1 polyethylene glycol membrane has a Cu-BTC@TpPa-1 core-shell structure, wherein a Cu-BTC shell structure is grown in situ on the surface of TpPa-1 with TpPa-1 as the core; the pore structure of the membrane product has small pores. - Large hole - small hole An ordered, hierarchical, multi-level porous structure is arranged, in which the total pore volume ratio of small pores to large pores is 0.2 to 0.8:1.

[0016] The present invention further provides a method for applying the Cu-BTC@TpPa-1 thermally crosslinked polyethylene glycol membrane prepared by the aforementioned method to separate CO2 in a mixed gas, which involves assembling the membrane into a flat sheet membrane module and using it for gas separation operations.

[0017] As a preferred embodiment of the present invention, the application method specifically includes the following steps:

[0018] (1) Place the Cu-BTC@TpPa-1 polyethylene glycol membrane into the flat sheet membrane module and press the edge of the membrane product with a rubber sealing ring to prevent air leakage; connect the air inlet pipe to one side of the flat sheet membrane module and the permeate pipe to the other side, and set the permeate pipe at the connection between the air inlet pipe and the flat sheet membrane module.

[0019] (2) Under the conditions of temperature 25~65℃ and total pressure 0.1~1.0MPa, a mixed gas with a CO2 volume concentration of 5~40% is sent into the inlet pipe, and the CO2 in the mixed gas is separated and removed by the flat sheet membrane module. After passing through the flat sheet membrane module, the CO2 gas is sent into the storage tank through the permeate pipe. Impurity gases that are difficult to permeate are retained upstream of the Cu-BTC@TpPa-1 polyethylene glycol membrane and discharged from the permeate pipe.

[0020] As a preferred embodiment of the present invention, the mixed gas further includes N2 with a volume concentration of 20-35%, H2 with a volume concentration of 10-30%, and CH4 with a volume concentration of 15-45%.

[0021] Description of the invention principle:

[0022] Cu-BTC is a typical metal-organic framework, composed of a copper metal center and trimesic acid as a ligand. After the coordination reaction, each Cu atom coordinates with a water molecule. By removing the water molecule through heating under vacuum, the active site is exposed, forming an open metal site, which is an active site capable of efficiently adsorbing specific molecules. However, while traditional Cu-BTC has open metal sites and can efficiently adsorb CO2, it has a small pore size, low pore volume, and high mass transfer resistance. In contrast, TpPa-1 has a large pore size, high pore volume, and low mass transfer resistance, but its selective adsorption of CO2 is weaker. If traditional MOF preparation technology is still used, even with Cu-BTC, the problem of easy accumulation in the membrane will still occur, resulting in a complex pore structure in the final membrane product and high resistance to gas molecule transport in non-porous areas.

[0023] This invention constructs an ordered, hierarchical, multi-layered core-shell Cu-BTC@TpPa-1 structure, organically combining the advantages of open metal sites in Cu-BTC and low mass transfer resistance in TpPa-1. This structure enables selective gas adsorption and accelerates gas transport, giving it a significant competitive advantage. Compared to traditional MOF mixed matrix membrane preparation techniques, this invention fully utilizes open metal sites, resulting in Cu-BTC exhibiting extremely high CO2 adsorption capacity and selectivity. Because Cu-BTC is loaded on the TpPa-1 surface, a sandwich-like structure of Cu-BTC—TpPa-1—Cu-BTC is formed. Comparing the radial dimensions of the channels, the channels in Cu-BTC are small pores, while those in TpPa-1 are large pores. Therefore, this sandwich-like structure forms an ordered, hierarchical, multi-layered porous structure of small pores-large pores-small pores.

[0024] This technological advantage is specifically manifested in the following ways: the core-shell hybrid MOF-in-COF constructed in this invention can improve the gas separation effect of porous materials in membranes. The MOF acts as a shell surrounding the COF core, and its internal microporous structure can function as a molecular sieve in gas separation. The pore structure in the membrane product has an ordered, hierarchical, multi-level pore structure, and is arranged according to… Small hole - Large hole - The pores are arranged in a microporous structure. Gases with larger molecular dynamic diameters are repelled from the outside of the MOF channels, while gases with smaller molecular dynamic diameters can enter the MOF channels and be transported into the COF channels. The macroporous environment in the COF provides a low mass transfer resistance channel for gas molecule transport, facilitating rapid gas passage.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] 1. This invention constructs a core-shell hybrid MOF in COF, which enhances the gas separation performance of porous materials in membranes. The MOF acts as a shell surrounding the COF core, and its internal microporous structure functions as a molecular sieve in gas separation. Gases with larger molecular dynamic diameters are repelled from the MOF channels, while gases with smaller molecular dynamic diameters can enter the MOF channels and be transported into the COF channels. The macroporous environment in the COF provides a low mass transfer resistance channel for gas molecule transport, facilitating rapid gas passage. Cu-BTC@TpPa-1 exhibits an ideal adsorption selectivity of 37 for CO2 and N2 at 298 K and 1 bar, respectively, representing improvements of 85% and 143% compared to pure Cu-BTC and pure TpPa-1.

[0027] 2. This invention uses Cu-BTC@TpPa-1 as a filler in a polyethylene glycol matrix to prepare a polyethylene glycol membrane, which effectively improves the solubility and diffusion of CO2 in the membrane. The strong affinity of the open metal sites on the Cu-BTC surface for CO2 molecules is utilized to enhance the solubility of CO2 molecules on the membrane surface. The ordered hierarchical multi-level porous structure of micropores-macropores-micropores is used to improve the selective diffusion of CO2 molecules within the membrane and reduce mass transfer resistance. The CO2 permeability and CO2 / N2 selectivity of the thermally crosslinked polyethylene glycol membrane loaded with 10 wt% Cu-BTC@TpPa-1 (TpPa-1:Cu-BTC = 1:5) were 897 and 52, respectively, exceeding the industry-recognized Robeson upper limit. The permeability was increased by 49.5% and 26.0% compared with the 10 wt% Cu-BTC loaded membrane and the 10 wt% TpPa-1 loaded membrane, respectively, and the selectivity was increased by 12.9% and 67.2% compared with the 10 wt% Cu-BTC loaded membrane and the 10 wt% TpPa-1 loaded membrane, respectively. Attached Figure Description

[0028] Figure 1 The flowchart shows the preparation process of the ordered, hierarchical, multi-level porous core-shell Cu-BTC@TpPa-1 composite adsorbent thermally crosslinked polyethylene glycol membrane of the present invention.

[0029] Figure 2 The process flow diagram shows the separation and removal of CO2 using Cu-BTC@TpPa-1 polyethylene glycol membrane.

[0030] Figure 3 Scanning electron microscope image of a core-shell Cu-BTC@TpPa-1 structure with ordered hierarchical pores. Detailed Implementation

[0031] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. These embodiments will enable those skilled in the art to gain a more comprehensive understanding of the present invention, but will not limit the invention in any way.

[0032] The method for preparing an ordered, hierarchical, multi-level porous core-shell Cu-BTC@TpPa-1 polyethylene glycol membrane provided by this invention is as follows: Figure 1 As shown. Specifically, it includes the following steps:

[0033] (1) According to the dosage relationship of 0.63g:0.48g:15ml:15ml:5ml, tricarboxymethyl phloroglucinol (Tp), p-phenylenediamine (Pa), mesitylene, dioxane and acetic acid aqueous solution with a concentration of 3mol / L were added to a heat-resistant glass container. After sonication until completely dissolved, the mixture was degassed by freeze-thaw cycle 3 times. The heat-resistant glass container was sealed and evacuated, and heated at 120℃ for 72 hours. The reaction precipitate was obtained by centrifugation. The solvent was first exchanged with tetrahydrofuran 3 times, 12 hours each time. Then the solvent was exchanged with acetone 3 times, 12 hours each time. The mixture was dried in a vacuum oven at 120℃ for 12 hours to obtain a dark red powdery covalent organic framework TpPa-1.

[0034] (2) Weigh TpPa-1 and polyvinylpyrrolidone (PVP) as a surfactant at a mass ratio of 2:1. First, dissolve TpPa-1 in an ethanol solution, then add polyvinylpyrrolidone (PVP) and stir for 2 hours. Dry in a vacuum oven at 120°C for 12 hours to obtain TpPa-1 loaded with PVP.

[0035] (3) Weigh out PVP-loaded TpPa-1, Cu(NO3)2·3H2O and mesitylene according to a mass ratio of 100:33~330:67~670 respectively; first disperse the PVP-loaded TpPa-1 in methanol, dissolve Cu(NO3)2·3H2O in deionized water, and dissolve mesitylene in ethanol solution, then mix and stir until uniform; introduce the mixture into a polytetrafluoroethylene reactor, react at 110℃ for 48 hours, and a copper-based metal-organic framework Cu-BTC is formed in situ on the surface of TpPa-1; collect the solid product by centrifugation, purify it several times with methanol; dry it in a vacuum oven at 120℃ for 12 hours to obtain Cu-BTC@TpPa-1 with a core-shell structure;

[0036] (4) Weigh Cu-BTC@TpPa-1, polyethylene glycol diacrylate (PEGDA) and azobisisobutyronitrile (AIBN) as a crosslinking agent according to a mass ratio of 20-220:1000:5, mix and stir thoroughly to obtain a mixture; spread the mixture on a glass plate, take another glass plate and press it on its surface, and use a 200μm thick spacer between the glass plates to control the film thickness; transfer the above components to a 70℃ oven for thermal crosslinking and plasticizing to obtain Cu-BTC@TpPa-1 polyethylene glycol film.

[0037] This membrane product features a Cu-BTC@TpPa-1 core-shell structure, where a Cu-BTC shell layer is grown in situ on the surface of Tppa-1, with Tppa-1 serving as the core. The membrane product exhibits an ordered, hierarchical, multi-level pore structure arranged in a "small pore-large pore-small pore" pattern, with the total pore volume ratio of small pores to large pores being 0.2–0.8:1.

[0038] In practical applications, this membrane product can be assembled into a flat sheet membrane module and used to separate CO2 from a mixed gas, specifically including the following steps:

[0039] (1) Place the Cu-BTC@TpPa-1 polyethylene glycol membrane into the flat sheet membrane module and press the edge of the membrane product with a rubber sealing ring to prevent air leakage; connect the air inlet pipe to one side of the flat sheet membrane module and the permeate pipe to the other side, and set the permeate pipe at the connection between the air inlet pipe and the flat sheet membrane module.

[0040] (2) Under the conditions of temperature 25-65℃ and total pressure 0.1-1.0MPa, a mixed gas with a CO2 volume concentration of 5-40% (including N2 with a volume concentration of 20-35%, H2 with a volume concentration of 10-30%, and CH4 with a volume concentration of 15-45%) is sent into the inlet pipe, and CO2 in the mixed gas is separated and removed by a flat sheet membrane module. After passing through the flat sheet membrane module, the CO2 gas is sent into the storage tank through the permeate pipe. Impurity gases that are difficult to permeate are retained upstream of the Cu-BTC@TpPa-1 polyethylene glycol membrane and discharged from the permeate pipe.

[0041] Example 1

[0042] Take a 100ml heat-resistant glass tube, add 0.63g triformylphloroglucinol (Tp), 0.48g p-phenylenediamine (Pa), 15ml mesitylene, 15ml dioxane, and 5ml acetic acid aqueous solution (3mol / L). Sonicate for 10 minutes until completely dissolved, then degas three times using a freeze-thaw cycle. Vacuum seal the glass tube and heat at 120℃ for 72 hours. Centrifuge to obtain the precipitate, exchange the solvent three times with tetrahydrofuran for 12 hours each time, then exchange the solvent three times with acetone for 12 hours each time. Finally, dry in a vacuum oven at 120℃ for 12 hours to obtain a dark red powdery covalent organic framework TpPa-1.

[0043] Weigh 0.2g of TpPa-1 and dissolve it in 10ml of ethanol solution. Add 0.1g of polyvinylpyrrolidone (PVP) as a surfactant. After stirring for 2 hours, dry in a vacuum oven at 120℃ for 12 hours to obtain TpPa-1 loaded with PVP.

[0044] 0.1 g of PVP-loaded TpPa-1 was dispersed in 10 mL of methanol to form solution A. 33 mg of Cu(NO3)2·3H2O was dissolved in 10 mL of deionized water to form solution B. 67 mg of mesitylene was dissolved in 10 mL of ethanol to form solution C. Solutions A, B, and C were mixed and stirred for 10 minutes until homogeneous. The mixture was then introduced into a polytetrafluoroethylene high-temperature and high-pressure reactor to grow a copper-based metal-organic framework (Cu-BTC) in situ on the surface of TpPa-1. After reacting at 110 °C for 48 hours, the product was collected by centrifugation. The product was washed three times with methanol and dried in a vacuum oven at 120 °C for 12 hours to obtain a core-shell structured Cu-BTC@TpPa-1.

[0045] like Figure 3 As shown in the scanning electron microscope image of Cu-BTC@TpPa-1 particles, Cu-BTC@TpPa-1 exhibits a core-shell structure. This structure has Tppa-1 as the core (marked in white in the figure), and a Cu-BTC shell structure is grown in situ on the surface of Tppa-1 (marked in yellow in the figure).

[0046] Weigh 20 mg of Cu-BTC@TpPa-1 and add it to 1 g of polyethylene glycol diacrylate (PEGDA). Then add 0.005 g of crosslinking agent azobisisobutyronitrile (AIBN) and stir thoroughly to obtain a mixed solution. Spread the mixed solution evenly on a glass plate, and press another glass plate on its surface. A 200 μm thick stainless steel blade is sandwiched between the two glass plates to control the film thickness. Place the above components in a 70°C oven to plasticize and shape the film, obtaining a Cu-BTC@TpPa-1 thermally crosslinked polyethylene glycol film.

[0047] The Cu-BTC@TpPa-1 thermally crosslinked polyethylene glycol mixed matrix membrane was placed in a flat sheet membrane module, and the membrane edges were sealed with rubber sealing rings to prevent air leakage. An inlet pipe was connected to the upper side of the flat sheet membrane module, and a permeate pipe was connected to the other end. A permeate gas pipe was installed at the connection between the inlet pipe and the flat sheet membrane module. Under conditions of 25°C and a total pressure of 0.1 MPa, a mixed gas with a CO2 volume concentration of 5% (including 20% ​​N2, 30% H2, and 45% CH4) was introduced into the gas membrane separation pipeline system. The flat sheet membrane module was used to separate and remove CO2 from the mixed gas. After passing through the flat sheet membrane module, the CO2 gas was sent to a storage tank through the permeate pipe. Impurities that were difficult to permeate were retained upstream of the mixed matrix membrane and discharged through the permeate gas pipe.

[0048] The membrane product of this invention features a layered pore structure, with pore diameters arranged sequentially from the inside out in a "small pore-large pore-small pore" pattern across different layers. Here, "large pore" and "small pore" refer to the relative size of the pore diameters within different layers. Since Cu-BTC is loaded onto the TpPa-1 surface, a sandwich-like structure of Cu-BTC—TpPa-1—Cu-BTC is formed. The pores in Cu-BTC are small pores, while those in TpPa-1 are large pores. Therefore, this sandwich-like structure creates an ordered, layered, multi-level pore structure of small pores-large pores-small pores. Analysis of the nitrogen adsorption and desorption isotherms of the membrane product in this embodiment using a porosimeter verifies that the membrane product possesses an ordered, layered, multi-level pore structure.

[0049] Testing revealed that the pore structure of the membrane product in this embodiment is based on... Small hole - Large hole - The membrane has a micropore arrangement, with a micropore to macropore total pore volume ratio of 0.2. The CO2 permeability coefficient of the membrane product is 768, and the CO2 / N2 selectivity is 47.

[0050] Example 2

[0051] Take a 100ml heat-resistant glass tube, add 0.63g triformylphloroglucinol (Tp), 0.48g p-phenylenediamine (Pa), 15ml mesitylene, 15ml dioxane, and 5ml acetic acid aqueous solution (3mol / L). Sonicate for 10 minutes until completely dissolved, then degas three times using a freeze-thaw cycle. Vacuum seal the glass tube and heat at 120℃ for 72 hours. Centrifuge to obtain the precipitate, exchange the solvent three times with tetrahydrofuran for 12 hours each time, then exchange the solvent three times with acetone for 12 hours each time. Finally, dry in a vacuum oven at 120℃ for 12 hours to obtain a dark red powdery covalent organic framework TpPa-1.

[0052] Weigh 0.2g of TpPa-1 and dissolve it in 10ml of ethanol solution. Add 0.1g of polyvinylpyrrolidone (PVP) as a surfactant. After stirring for 2 hours, dry in a vacuum oven at 120℃ for 12 hours to obtain TpPa-1 loaded with PVP.

[0053] 0.1 g of PVP-loaded TpPa-1 was dispersed in 10 mL of methanol to form solution A. 165 mg of Cu(NO3)2·3H2O was dissolved in 10 mL of deionized water to form solution B. 335 mg of mesitylene was dissolved in 10 mL of ethanol to form solution C. Solutions A, B, and C were mixed and stirred for 10 minutes until homogeneous. The mixture was then introduced into a polytetrafluoroethylene high-temperature and high-pressure reactor to grow a copper-based metal-organic framework (Cu-BTC) in situ on the surface of TpPa-1. After reacting at 110 °C for 48 hours, the product was collected by centrifugation. The product was washed three times with methanol and dried in a vacuum oven at 120 °C for 12 hours to obtain a core-shell structured Cu-BTC@TpPa-1.

[0054] Weigh 110 mg of Cu-BTC@TpPa-1 and add it to 1 g of polyethylene glycol diacrylate (PEGDA). Then add 0.005 g of crosslinking agent azobisisobutyronitrile (AIBN) and stir thoroughly to obtain a mixed solution. Spread the mixed solution evenly on a glass plate, and press another glass plate on its surface. A 200 μm thick stainless steel blade is sandwiched between the two glass plates to control the film thickness. Place the above components in a 70°C oven to plasticize and shape the film, obtaining a Cu-BTC@TpPa-1 thermally crosslinked polyethylene glycol film.

[0055] The Cu-BTC@TpPa-1 thermally crosslinked polyethylene glycol mixed matrix membrane was placed in a flat sheet membrane module, and the membrane edges were sealed with rubber sealing rings to prevent air leakage. An inlet pipe was connected to the upper side of the flat sheet membrane module, and a permeate pipe was connected to the other end. A residual permeate pipe was installed at the connection between the inlet pipe and the flat sheet membrane module. Under conditions of 45°C and a total pressure of 0.5 MPa, a mixed gas with a CO2 volume concentration of 20% (including 30% N2, 20% H2, and 30% CH4) was introduced into the gas membrane separation pipeline system. The flat sheet membrane module was used to separate and remove CO2 from the mixed gas. After passing through the flat sheet membrane module, the CO2 gas was sent to a storage tank through the permeate pipe. Impurities that were difficult to permeate were retained upstream of the mixed matrix membrane and discharged through the residual permeate pipe.

[0056] Testing revealed that the membrane product in this embodiment possesses an ordered, hierarchical, multi-level pore structure, and is arranged according to... Small hole - Large hole - The membrane has a pore arrangement with a total pore volume ratio of 0.5 between small and large pores. The CO2 permeability coefficient of the membrane product is 897, and the CO2 / N2 selectivity is 52.

[0057] Example 3

[0058] Take a 100 ml heat-resistant glass tube, add 0.63 g triformylphloroglucinol (Tp), 0.48 g p-phenylenediamine (Pa), 15 ml mesitylene, 15 ml dioxane, and 5 ml acetic acid aqueous solution (3 mol / L). Sonicate for 10 minutes until completely dissolved, then degas three times using a freeze-thaw cycle. Vacuum seal the glass tube and heat at 120 °C for 72 hours. Centrifuge to obtain the precipitate, exchange the solvent three times with tetrahydrofuran for 12 hours each time, then exchange the solvent three times with acetone for 12 hours each time. Finally, dry in a vacuum oven at 120 °C for 12 hours to obtain a dark red powdery covalent organic framework TpPa-1.

[0059] Weigh 0.2g of TpPa-1 and dissolve it in 10ml of ethanol solution. Add 0.1g of polyvinylpyrrolidone (PVP) as a surfactant. After stirring for 2 hours, dry in a vacuum oven at 120℃ for 12 hours to obtain TpPa-1 loaded with PVP.

[0060] 0.1 g of PVP-loaded TpPa-1 was dispersed in 10 mL of methanol to form solution A. 330 mg of Cu(NO3)2·3H2O was dissolved in 10 mL of deionized water to form solution B. 670 mg of mesitylene was dissolved in 10 mL of ethanol to form solution C. Solutions A, B, and C were mixed and stirred for 10 minutes until homogeneous. The mixture was then introduced into a polytetrafluoroethylene high-temperature and high-pressure reactor to grow a copper-based metal-organic framework (Cu-BTC) in situ on the surface of TpPa-1. After reacting at 110 °C for 48 hours, the product was collected by centrifugation. The product was washed three times with methanol and dried in a vacuum oven at 120 °C for 12 hours to obtain a core-shell structured Cu-BTC@TpPa-1.

[0061] Weigh 220 mg of Cu-BTC@TpPa-1 and add it to 1 g of polyethylene glycol diacrylate (PEGDA). Then add 0.005 g of crosslinking agent azobisisobutyronitrile (AIBN) and stir thoroughly to obtain a mixed solution. Spread the mixed solution evenly on a glass plate, and press another glass plate on its surface. A 200 μm thick stainless steel blade is sandwiched between the two glass plates to control the film thickness. Place the above components in a 70°C oven to plasticize and shape the film, obtaining a Cu-BTC@TpPa-1 thermally crosslinked polyethylene glycol film.

[0062] The Cu-BTC@TpPa-1 thermally crosslinked polyethylene glycol mixed matrix membrane was placed in a flat sheet membrane module, and the membrane edges were sealed with rubber sealing rings to prevent air leakage. An inlet pipe was connected to the upper side of the flat sheet membrane module, and a permeate pipe was connected to the other end. A permeate gas pipe was installed at the connection between the inlet pipe and the flat sheet membrane module. Under conditions of 65°C and a total pressure of 1 MPa, a mixed gas with a CO2 volume concentration of 40% (including 35% N2, 10% H2, and 15% CH4) was introduced into the gas membrane separation pipeline system. The flat sheet membrane module was used to separate and remove CO2 from the mixed gas. After passing through the flat sheet membrane module, the CO2 gas was sent to a storage tank through the permeate pipe. Impurities that were difficult to permeate were retained upstream of the mixed matrix membrane and discharged through the permeate gas pipe.

[0063] Testing revealed that the membrane product in this embodiment possesses an ordered, hierarchical, multi-level pore structure, and is arranged according to... small hole

[0064] - Large hole - The membrane has a pore arrangement with a total pore volume ratio of 0.8 between small and large pores. The CO2 permeability coefficient of the membrane product is 801, and the CO2 / N2 selectivity is 67.

[0065] Finally, it should be noted that the above examples are merely specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments and many variations are possible. All variations that can be directly derived or conceived by those skilled in the art from the disclosure of this invention should be considered within the scope of protection of this invention.

Claims

1. The application of an ordered, hierarchical, multi-level porous core-shell Cu-BTC@TpPa-1 polyethylene glycol membrane in the separation of CO2 in a mixed gas, characterized in that, The membrane is assembled into a flat-sheet membrane module and used for gas separation operations; The preparation method of the core-shell Cu-BTC@TpPa-1 polyethylene glycol membrane includes the following steps: (1) Take 0.63g:0.48g:15ml:15ml:5ml, add triformyl phloroglucinol, p-phenylenediamine, mesitylene, dioxane and acetic acid aqueous solution with a concentration of 3mol / L to a heat-resistant glass container; sonicate until completely dissolved, and degas 3 times by freeze-thaw cycle; seal the heat-resistant glass container and evacuate it, and heat it at 120℃ for 72 hours; obtain the reaction precipitate by centrifugation, wash it several times with tetrahydrofuran and acetone respectively; after vacuum drying, obtain a dark red powdery covalent organic framework TpPa-1; (2) Weigh TpPa-1 and polyvinylpyrrolidone as a surfactant at a mass ratio of 2:1; dissolve TpPa-1 in ethanol solution first, then add polyvinylpyrrolidone and stir for 2 hours; after vacuum drying, obtain TpPa-1 loaded with PVP. (3) Weigh out TpPa-1 loaded with PVP, Cu(NO3)2·3H2O and mesitylene respectively in a mass ratio of 100:33~330:67~670; first disperse TpPa-1 loaded with PVP in methanol, dissolve Cu(NO3)2·3H2O in deionized water, dissolve mesitylene in ethanol solution, then mix and stir until uniform; introduce the mixture into a polytetrafluoroethylene reactor, react at 110℃ for 48 hours, and a copper-based metal-organic framework Cu-BTC is grown in situ on the surface of TpPa-1; collect the solid product by centrifugation, and purify it several times with methanol; after vacuum drying, obtain Cu-BTC@TpPa-1 with a core-shell structure; (4) Weigh Cu-BTC@TpPa-1, polyethylene glycol diacrylate and azobisisobutyronitrile (AIBN) used as a crosslinking agent according to a mass ratio of 20~220:1000:5, mix and stir thoroughly to obtain a mixture; spread the mixture on a glass plate, press another glass plate on its surface, and use a spacer between the glass plates to control the film thickness; transfer the above components to a 70℃ oven for thermal crosslinking and plasticizing to obtain Cu-BTC@TpPa-1 polyethylene glycol membrane; the pore structure in the membrane product has an ordered hierarchical multi-level pore structure arranged in the order of small pore-large pore-small pore, wherein the total pore volume ratio of small pores to large pores is 0.2~0.8:

1.

2. The application according to claim 1, characterized in that, In steps (1) to (3), vacuum drying refers to drying in a vacuum oven at 120°C for 12 hours.

3. The application according to claim 1, characterized in that, In step (1), the cleaning operation includes: first, exchanging the solvent with tetrahydrofuran 3 times, each time for 12 hours; then exchanging the solvent with acetone 3 times, each time for 12 hours.

4. The application according to claim 1, characterized in that, In step (4), the thickness of the gasket is 200 μm.

5. The application according to claim 1, characterized in that, The Cu-BTC@TpPa-1 polyethylene glycol film has a Cu-BTC@TpPa-1 core-shell structure, which is a Cu-BTC shell structure grown in situ on the surface of Tppa-1 with Tppa-1 as the core.

6. The application according to claim 1, characterized in that, Specifically, the following steps are included: (1) Place the Cu-BTC@TpPa-1 polyethylene glycol membrane into the flat sheet membrane module and press the edge of the membrane product with a rubber sealing ring to prevent air leakage; connect the air inlet pipe to one side of the flat sheet membrane module and the permeate pipe to the other side, and set the permeate pipe at the connection between the air inlet pipe and the flat sheet membrane module. (2) Under the conditions of temperature 25~65℃ and total pressure 0.1~1.0MPa, a mixed gas with a CO2 volume concentration of 5~40% is sent into the inlet pipe, and the CO2 in the mixed gas is separated and removed by the flat sheet membrane module. After passing through the flat sheet membrane module, the CO2 gas is sent into the storage tank through the permeate pipe. Impurity gases that are difficult to permeate are retained upstream of the Cu-BTC@TpPa-1 polyethylene glycol membrane and discharged from the permeate pipe.

7. The application according to claim 1, characterized in that, The mixed gas also includes N2 with a volume concentration of 20-35%, H2 with a volume concentration of 10-30%, and CH4 with a volume concentration of 15-45%.

Citation Information

Patent Citations

  • Preparation method of copper-nickel zeolite imidazolate loaded polyimide gel mixed matrix membrane

    CN111841344A

  • Preparation method and application of PLNPs-COFs composite photocatalytic material with core-shell structure

    CN117101720A